Response Time Analysis of Fire and Rescue Services in Collaboration with Nottinghamshire Fire & Rescue Service - Tan, Melis (2019)
Fire and emergency service response times have been increasing in recent years, thus response time analysis has become more attractive for researchers. Although some researchers have identified the causes of this increase, it could not be prevented thus far. This study analyses the factors affecting response time with regard to increased collaboration with Nottinghamshire Fire and Rescue Service in the UK. Descriptive statistics and multiple regression are used to analyse incident records for two years. The study found that vehicle status, distance, and pumping appliances status have a great impact on response time.